Implementasi Sistem Aplikasi Agent Anywhere Pada PT. Bank Syariah Indonesia Terintegrasi Whatsapp Menggunakan Metode Agile Scrum - Sugiarto, Hady; Kuntoro, Antonius Yadi (Jurnal Ilmu Komputer (JUIK), 2024)
In recent years, information and communication systems have experienced rapid growth. The impact is not only felt by those working in technology, but also affects the lifestyles of people from all walks of life. The emergence of online marketing is one of the impacts of these technological advances. As time goes by, many companies are forced to lay off their employees for reasons of age, especially those who are married and have children, even though basically these employees are still very productive in their fields. Agent Anywhere is a strategy of using online platforms to communicate messages about business image, as well as promote products or services to potential consumers. The online platforms used are very diverse, ranging from websites, search engine optimization (SEO) techniques, pay per click (PPC) advertising, marketing via email (email marketing), to social networks, in designing applications as promotional and information media. Online Marketing consists of two pages, the admin page and the Agent page. Agents can access and log in first. In this application, agents can send promotional messages directly by creating a campaign/activity first and preparing Leads data as a Whatsapp telephone number database. This application is designed using the programming languages PHP, CodeLignter, XAMPP, Node.js, and MySql as the database.